AB0960 THE HELIOS (HACETTEPE UNIVERSITY ELECTRONIC RESEARCH FORMS) REGISTRY: USE OF BIOLOGIC DRUGS IN AUTOINFLAMMATORY DISEASES. (June 2019) - Demir, Selcan; Batu, Ezgi Deniz; Akal, Fuat; Sag, Erdal; Akca, Ummusen Kaya; Arslanoğlu, Elif; Aliyev, Emil; Yüksel, Kübra; Keskin, Armağan; Bilginer, Yelda; özen, Seza
Abstract : Background: Autoinflammatory diseases (AID) are characterized by a dysregulation of innate immunity leading to uncontrolled inflammation. The treatment in AID is critical to control the disease activity, to prevent complications, and to improve the health-related quality of life. Biologic drugs have revolutionized the treatment and outcomes in AID. Objectives: Herein we aim to present the clinical characteristics of children to whom biologic drug therapy was initiated for the management of AID. Methods: A web-based registry called the Helios Registry (Hacettepe univErsity eLectronIc research fOrmS) has been formed to evaluate the data of all children on biologic treatment. We have been enrolling patients since August 2018 retrospectively and prospectively. We have analyzed the data about the general characteristics of the patients, treatment, the biologic drug used, and adverse effects. Only the patients with the following diagnoses were included: systemic juvenile idiopathic arthritis (SJIA ), familial Mediterranean fever (FMF), cryopyrin associated periodic syndrome (CAPS), and chronic recurrent multifocal osteomyelitis (CRMO). Results: Of 60 patients included, 19 had FMF (31.7%), 24 had sJIA (40%), 10 had CAPS, (16.7%), and 7 had CRMO (11.7%). Their median age was 10.7 (2-20) years old and disease duration was 2.8 (0-6) years, at the time of biologic drug initiation. 58.3% were currently on canakinumab, 20% anakinra, 10% tocilizumab, 10% etanercept, and 1.7% adalimumab. 63.3% of our patients had previously used at least one other biologic drug. The rate of glucocorticoid use before biologic treatment was 56.6%. The median duration of glucocorticoid treatment after initiating biologic drugs was 7.4 months. 56 (93%) patients achieved remission on biologic therapy. There were 15 patients (25%) who received tuberculosis prophylaxis due to positive tuberculin skin test (diameter≥10 mm) and there was no Quantiferon test positivity. Thirteen adverse events (AE) had been noted. 2 of them were serious events as anaphylaxis due to tocilizumab infusions. The rest of the adverse events were mild thrombocytopenia (n=2), varicella infection (n=1), and local side effects (n=8). The median number of the infections per year was one and there were no death or malignancy. Conclusion: The most commonly prescribed biologic drugs were IL-1 inhibitors especially for patients with IL-1-mediated AID (FMF, CAPS, and SJIA). The biologic treatment in AID is effective and there were no serious side effects. References: [1] Ozen S, Bilginer Y. A clinical guide to autoinflammatory diseases: familial Mediterranean fever and next-of-kin. Nat Rev Rheumatol. 2014 Mar;10(3):135-47. doi:10.1038/nrrheum.2013.174 Disclosure of Interests: Selcan Demir: None declared, Ezgi Deniz Batu: None declared, Fuat Akal: None declared, Erdal Sag: None declared, Ummusen Kaya Akca: None declared, Elif Arslanoğlu: None declared, Emil Aliyev: None declared, Kübra Yüksel: None declared, Armağan Keskin: None declared, Yelda Bilginer: None declared, Seza özen Consultant for: Seza Ozen is receiving consultancy fees from Novartis, Speakers bureau: Roche